FAKTOR-FAKTOR YANG MEMPENGARUHI VOLATILITAS HARGA SAHAM PADA PERUSAHAAN PUBLIK NONKEUANGAN - ANASTASSIA ANASTASSIA; FRISKA FIRNANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this study is to obtain empirical evidence of the effect offactors on share price volatility in go-public non-financial companies that listed on the Indonesian Stock Exchange. The factors are dividend yield, dividend payout ratio, firm size, earnings volatility, debt to asset ratio, growth in asset and book value per share. Seventy six companies were used as sample. The data were collected from financial report over the four eight period 2009-2012. Hypothesis tested by using multiple regression analysis. The results of this study indicate that earnings volatility and debt to asset ratio have no effect on share price volatility. However, dividend yield has significant positive effect on share price volatility. While, dividend payout ratio, firm size, growth in asset and book value per share has significant negative effect on share price volatility.